Pengaruh Pengangguran dan Jumlah Penduduk Terhadap Kemiskinan di Provinsi Lampung 2018-2021 - Abi Reza Alfikri; Diva Okta Nadia; Rama Harfi Ferdinan; Misfi Laili Rohmi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Poverty is a problem that continues to be faced by both developed and developing countries. In developing countries with high population density, this problem is very difficult to overcome, because the increasing population not only has an impact on the economic sector, but also political instability. This research aims to determine the effect of unemployment and population on poverty in Lampung Province. This data was obtained from BPS publications for the 2019-2021 period. This research uses panel data regression analysis and produces that partially unemployment (X1) has no significant effect on poverty (Y). population (X2) has no effect on poverty (Y). Meanwhile, together, unemployment and population have no effect on poverty.